2022
DOI: 10.1186/s40168-022-01260-9
|View full text |Cite
|
Sign up to set email alerts
|

Human endogenous retrovirus K in the respiratory tract is associated with COVID-19 physiopathology

Abstract: Background Critically ill 2019 coronavirus disease (COVID-19) patients under invasive mechanical ventilation (IMV) are 10 to 40 times more likely to die than the general population. Although progression from mild to severe COVID-19 has been associated with hypoxia, uncontrolled inflammation, and coagulopathy, the mechanisms involved in the progression to severity are poorly understood. Methods The virome of tracheal aspirates (TA) from 25 COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 83 publications
1
31
0
Order By: Relevance
“…On the other hand, 75.00% (9/12) of severe/moderate and 25.00% (3/12) of healthy/asymptomatic/mild COVID‐19 cases HERV‐K113‐ENV is transcriptionally inactive (Figure 1F,G ). Interestingly, the role of HERV‐K113 in SARS‐CoV‐2 cases in the Brazilian population has also been reported, 2 further our analysis of Brazilian transcriptomes revealed that 60% (15/25) diseased/discharged cases of HERV‐K113‐ENV seem to be transcriptionally inactive, but transcriptionally active in 80% (4/5) non‐COVID‐19 cases. Collectively, the risk of hospitalization for COVID‐19‐positive humans becoming a severe/moderate condition is largely eliminated until the HERV‐K113‐ENV component is actively transcribed.…”
Section: Figuresupporting
confidence: 67%
“…On the other hand, 75.00% (9/12) of severe/moderate and 25.00% (3/12) of healthy/asymptomatic/mild COVID‐19 cases HERV‐K113‐ENV is transcriptionally inactive (Figure 1F,G ). Interestingly, the role of HERV‐K113 in SARS‐CoV‐2 cases in the Brazilian population has also been reported, 2 further our analysis of Brazilian transcriptomes revealed that 60% (15/25) diseased/discharged cases of HERV‐K113‐ENV seem to be transcriptionally inactive, but transcriptionally active in 80% (4/5) non‐COVID‐19 cases. Collectively, the risk of hospitalization for COVID‐19‐positive humans becoming a severe/moderate condition is largely eliminated until the HERV‐K113‐ENV component is actively transcribed.…”
Section: Figuresupporting
confidence: 67%
“…In a small sample of critically ill patients, however, five of ten showed an increase in viral abundance, including viruses EBV, CMV, TTV, HSV, HPVB19, and JCV [ 86 ]. Additionally, an examination of the human endogenous retrovirus K found increased expression in endotracheal aspirate from intubated COVID-19 compared to intubated non-COVID-19 patients, but found no difference in outcome within COVID-19 [ 87 ]. Finally, Merenstein and colleagues found elevated levels of the commensal DNA virus Anelloviridae and recently described Redondoviridae in the oropharynx of intubated relative to non-intubated COVID-19 patients [ 64 ].…”
Section: Associations Of Covid-19 With Microbial Constituents Other T...mentioning
confidence: 99%
“…Most HERVs are silent in healthy adult cells and tissues, but proviral RNAs or proteins were observed in several diseases, such as inflammation, autoimmune diseases, and malignancies ( Grandi and Tramontano, 2018a ; Tokuyama et al, 2018 ; Licastro and Porcellini, 2021 ). Recently, several studies reported that HERV-K expression was increased after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection both in vivo and in vitro ( Guo et al, 2022 ; Temerozo et al, 2022 ). Interestingly, evidence showed that HERV activity correlated with cell proliferation.…”
Section: Human Endogenous Retroviruses and Their Physiological Expres...mentioning
confidence: 99%